Financial Ratios and Probability of Default by Using the KMV-Merton Method in the Non-Financial Sector listed on the Indonesia Stock Exchange - D. Malasari; M. Adam; . Yuliani; A. Hanafi (Финансы: теория и практика, 2020)
This study aims to analyze the predictions of the default probability in the non-financial sector of the Indonesia Stock Exchange and the mutual influence between financial ratios. The KMV–Merton method was used for the calculations. The study was conducted on the example of data from 18 companies listed on the Indonesia Stock Exchange. The scientific materials and documentation were analyzed with the help of the EViews. The authors made the followingconclusions: Return on Equity (ROE) has no effect on the probability of default; Current Ratio (CR) has no effect on the probability of default; Debt to Equity Ratio (DER) has a positive effect on the probability of default; Total Assets Turnover (TAT) has a negative effect on the probability of default.